Pogostnostna analiza besed iz elektonskega korpusa slovenskih besed - Grzybek, Peter (Slavistična revija, 2000)
The article deals with quantitative analysis of lexical lenght and frequency in Slovene and with related questions. The analysis goes beyond the limits of practical use, but at the same time it is illustrative enough to programmatically point out various research options that have so far not been in Slovene linguistics and literary criticism.
Keywords: korpusno jezikoslovje; leksikologija; slovenščina; zbirke besedil